A comparative study of different control algorithm used in unified power quality conditioner for power quality improvement. (17th February 2021) - Gupta, Nikita; Seethalekshmi, K.
Demand for power is on constant increase and it has necessitated the use of alternative energy sources that are discrete in nature and need conversion for utilisation. For this conversion, use of the semiconductor devices is indispensable, which has its own technical challenges and one among them is power quality (PQ). PQ has gained a widespread attention with the increase in penetration level of distributed generation (DG). Integration of DG sources in the grid introduces PQ issues like harmonics, flickers, voltage swells and sags in the system. Unified power quality conditioner (UPQC) is identified to be a reliable and efficient flexible AC transmission systems (FACTS) controller to mitigate the power quality problems. UPQC is based on a hybrid technology that consists of series and shunt inverters connected via a DC link that provide voltage compensation and current compensation. Characteristics of the UPQC are dependent on embedded control algorithm, which ensures proper voltage regulation at DC link and capacitor-voltage equalisation. This paper compares the control algorithms utilised in UPQC for generating reference signals for providing voltage and current compensation, with a special emphasis to total harmonic distortion (THD).